SMARCA4-deficient undifferentiated carcinoma co-existing with primary endometrial gastric (or gastrointestinal) -type carcinoma: a case report - Yang, Fan; Fu, Haixiao; Zheng, Xiang; Yang, Yuzhong; Zhou, Quyan; Liang, Yuanna; Zheng, Jinhua; Lin, Jing (Frontiers in Oncology, 2025)
Dedifferentiated endometrial carcinoma (DEC) is a rare and highly malignant endometrial tumor consisting of both undifferentiated endometrial carcinoma (UEC) and differentiated components (that are typically grade 1 or 2 endometrioid carcinomas). By contrast, the coexistence of UEC with a high-grade endometrial carcinoma has not been well reported. Primary endometrial gastric (gastrointestinal)-type carcinoma (PEGT-carcinoma) is a newly classified and rare type of female genital tract cancer, this neoplasm belongs to high-grade endometrial carcinoma and tends to have a poor outcome. In this study, we reported an atypical case of DEC composed of SMARCA4-deficient UEC and PEGT-carcinoma and reviewed its clinicopathological features.